MONITORING IRON TOXICITY-MEDIATED ORGAN DAMAGE IN β-THALASSEMIA MAJOR PATIENTS: ROLE OF HEPCIDIN AND FERRITIN (Applied Biological Research, 2026)
Post-transfusion iron toxicity in β-thalassemia major can lead to organ damage, which may include injury to the liver and kidneys. Monitoring the iron levels through hepcidin is crucial for patients due to thalassemia. This study was aimed to assess correlation between serum ferritin and hepcidin, and evaluate their role in tracking iron availability following frequent transfusions in these patients. Thirty subjects (19 males and 11 females) suffering β-thalassemia were chosen at Brainware Diagnostic & Research Center, Kolkata, West Bengal (India) against 15 normal individuals. The medical records of patients were examined by using standard criteria. Hematological parameters were recorded, and biochemical assessment was done for serum ferritin, hepcidin, TIBC, LFT, and RFT. The results showed lower RBC indices and notably higher serum ferritin and hepcidin levels in thalassemic patients than in controls. ALP, AST, and ALT levels in patients were 79.03 ± 10.82, 67.12 ± 11.13, and 253.18 ± 22.01 IU L-1, respectively. Significantly (p
Keywords: β-Thalassemia, blood transfusion, ferritin, hepcidin, iron toxicity, kidney function, liver function